The Influence of Digital Marketing on MSME Marketing in the Polmed Canteen - Apriana, Widya; Sutanto, Larasati Amanda; Lutfia, Zahwa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The sophistication of technology in today’s digital era is widely felt by all of us. This sophistication is not only seen in platforms but also in market structures that continue to evolve over time. Without realizing it, the expansion of the digital market has penetrated and grown everywhere. Digitalization has changed the way transactions and marketing are conducted. MSMEs not only have to compete with other MSMEs but are also expected to utilize digital marketing. This study focuses on the extent to which the MSME canteen at the Medan State Polytechnic utilizes digital marketing and is expected to serve as a reference for better research literature.